A comparison of race‐related pain stereotypes held by White and Black individuals. Issue 12 (17th October 2016) - Hollingshead, Nicole A.; Meints, Samantha M.; Miller, Megan M.; Robinson, Michael E.; Hirsh, Adam T.
Abstract: Pain judgments are the basis for pain management. The purpose of this study was to assess Black and White participants' race‐related pain stereotypes. Undergraduates ( n  = 551) rated the pain sensitivity and willingness to report pain for the typical Black person, White person, and themselves. Participants, regardless of race, rated the typical White person as being more pain sensitive and more willing to report pain than the typical Black person. White participants rated themselves as less sensitive and less willing to report pain than same‐race peers; however, Black participants rated themselves as more pain sensitive and more willing to report pain than same‐race peers. These findings highlight similarities and differences in racial stereotypic pain beliefs held by Black and White individuals.